Therapeutic Communication for Reducing Thesis Procrastination to The Students of Islamic Guidance and Counseling Departement UIN Sunan Ampel Surabaya (Jurnal Bimbingan dan Konseling Islam, 2021)
In this study, researchers will discuss about the communication used in the practice of guidance and counseling theraphy also known as therapeutic communication. The target of this study are students of the last semester Program  Islamic  Guidance and Counseling in  UIN Sunan Ampel Surabaya for  2015-2016 academic year. In general, students have  a study period around 3.5 years up to 4 years. But not all students can finish their thesis on time.  So, it makes an unrest effect on them. This occurs because it tends to delay their thesis.  As a result, many students are unable to finish the thesis program within the specified time for their graduation. Therefore, there needs to be an effort to guide academic procrastination among these students.  The BKI Program provides a consultation, namely Islamic Counseling Guidance. The purpose of this counseling guidance is to help student, so they don’t give up easily in terms of facing their problem. Like educational problems or personal problems (external or internal) and to help individuals maintain and develop good situations so as not to become a source of problems for themselves and others. Therefore, the method used in this counseling emphasized on politeness in language to provide guidance or advice to the students. The method used in this research is descriptive qualitative with survey approach. This research refers to the problems or facts that occur. The technique of collecting data are by survey, interview and treatment.